Technological and industrial trends in China’s pharmaceutical sector - Wang, Ju; He, Mengshan; Lu, Fengying; Chen, Ying; Wang, Hongguang (Frontiers in Pharmacology, 2025)
In recent years, China’s pharmaceutical industry has experienced rapid growth, positioning itself as the world’s second-largest pharmaceutical market and R&D hub. However, the industry faces significant challenges due to policy shifts and the effects of a “capital winter”. This paper provides a comprehensive analysis of the key trends shaping the future of China’s pharmaceutical sector, focusing on the impact of emerging technologies, such as precision medicine and synthetic biology, on drug development processes. It also examines changes in market demand for advanced formulations, chronic disease treatments, and rare disease drugs. Additionally, the paper explores the primary drivers and barriers to the industrial transformation from the perspectives of population aging, industrial restructuring, and internationalization. The findings suggest that technological innovation and industrial upgrading are critical to driving high-quality development in drug research and manufacturing. Achieving this requires coordinated efforts in policy optimization and corporate innovation to overcome technological barriers and promote sustainable, global growth. This study offers theoretical insights and practical recommendations for policymakers and corporate strategists in fostering long-term innovation and competitive advantage in the pharmaceutical industry.